2019
DOI: 10.3389/fmars.2019.00319
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Single Turnover Active Fluorometry (STAF) for the Estimation of Phytoplankton Primary Productivity (PhytoPP)

Abstract: is the ultimate source of reducing power for phytoplankton primary productivity (PhytoPP). Single turnover active chlorophyll fluorometry (STAF) provides a non-intrusive method that has the potential to measure PhytoPP on much wider spatiotemporal scales than is possible with more direct methods such as 14 C fixation or O 2 evolved through water oxidation. Application of a STAF-derived absorption coefficient for PSII light-harvesting (a LHII) provides a method for estimating PSII photochemical flux on a unit v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 40 publications
0
42
1
Order By: Relevance
“…Moreover, from the point of view of implementing a method of parameter assignment for remote sensing applications, of the variables listed above, only sea-surface temperature can be retrieved directly from space. As the gaps in our knowledge of the biotic and abiotic factors governing variation in the PE parameters are slowly being filled by conventional 14 C productivity experiments conducted at sea, there is also the potential of acquiring information on the photosynthetic characteristics of marine phytoplankton in a non-intrusive manner and over wider spatio-temporal scales using single turnover active chlorophyll fluorometry [ 39 ], although the conversion of electron transport rates into primary productivity estimates remains a challenge [ 23 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, from the point of view of implementing a method of parameter assignment for remote sensing applications, of the variables listed above, only sea-surface temperature can be retrieved directly from space. As the gaps in our knowledge of the biotic and abiotic factors governing variation in the PE parameters are slowly being filled by conventional 14 C productivity experiments conducted at sea, there is also the potential of acquiring information on the photosynthetic characteristics of marine phytoplankton in a non-intrusive manner and over wider spatio-temporal scales using single turnover active chlorophyll fluorometry [ 39 ], although the conversion of electron transport rates into primary productivity estimates remains a challenge [ 23 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of PSII reaction center (RCII, nmol m −3 ) was estimated fluorometrically according to Oxborough et al [28] as follows: where K R is an instrument-specific constant (photons m −3 s −1 ), F o is the fluorescence intensity at the zeroth flashlet of a single turnover measurement when all RCII are open, and σ PSII is the absorption cross section of PSII photochemistry under dark (m 2 ). A recent study showed K R / E FRRf can vary among phytoplankton taxonomic group and growth condition, and affect estimation of productivity [62]. In this study, we did not examine sample-specific K R / E FRRf values.…”
Section: Methodsmentioning
confidence: 91%
“…A recent study by Boatman et al. (2019) demonstrated that packaging of chlorophyll and light‐harvesting pigments into phytoplankton cells, referred to as the “package effect” (Kirk 1975, Bricaud et al. 1995) represents a potential source of error when calculating ETR PSII (and hence Φ e,C ) when using fluorometric estimation of [RCII] (FRRf) (e.g., Oxborough et al.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this error arises when applying an instrument‐specific constant, K a , (m −1 ) not corrected to account for reabsorption of photons generated by PSII fluorescence within the cell before exiting, a phenomenon that increases in magnitude with increasing package effect (Boatman et al. 2019). While a corrective procedure is described by Boatman et al.…”
Section: Discussionmentioning
confidence: 99%